EFFECTIVENESS OF COOPERATIVE LEARNING TYPE TAI (TEAM-ASSISTED INDIVIDUALIZATION) AND NHT (NUMBER HEAD TOGETHER) TYPE AGAINST MATHEMATICS LEARNING OUTCOMES OF SMPN 3 JETIS - Moh Rizki Yuniardi Basuni; Aris Thobirin (Universitas Ahmad Dahlan, 2017)
The study was conducted on the grounds that learning commonly applied in Jetis Middle School 3 in Bantul Regency tends to be teacher-centered, students become passive and less involved in the learning process, so learning models that involve students are needed. One learning model that can provide opportunities for students to be active in the Cooperative Learning Model Type TAI (Team-Assisted Individualization) and NHT type (Number Head Together). This study aims to determine the effectiveness of Cooperative Learning Type TAI (Team-Assisted Individualization) and NHT type (Number Head Together) on the mathematics learning outcomes of class VII students of SMP N 3 Jetis Bantul district, even semester 2015/2016 academic year on the subject of flat building rectangular. The population in this study were all VII graders in the even semester of SMP N 3 Jetis, Bantul Regency in the 2015/2016 academic year which were divided into 7 classes namely VII A, VII B, VII C, VII D, VII E, VII F, and VII G which a total of 212 students. The samples were taken in 3 classes with a purposive sampling technique, obtained class VII B as Experiment Class I, class VII A as Experimental Class II, and Class VII C as Control Class. The data analysis technique used for the prerequisite test includes the normality test with the Chi-Square formula, the homogeneity test with the Bartlett test, and the hypothesis test includes the F Test and the Least Significant Different (LSD) test. The results at a significant level of 5% and df = (2, 94) indicate (1) that at least two classes have differences in mathematics learning outcomes of students who use the Cooperative Learning Model Type TAI, NHT type, and direct learning models. This is indicated by the value so and (2) Classes that use the Cooperative learning model Type TAI are more effective than those using the NHT type learning model on learning outcomes and classes that use NHT type learning are more effective than those that use direct learning models on learning outcomes. This is indicated by the results of the LSD hypothesis test where a significant level of 5% and 94 degrees of freedom were obtained in case I = 7,92 and LSD = 6,35 so then > LSD then rejected and = 80,00 and = 72,08 means . In case II = 15,625 and LSD = 6,35 so then > LSD then rejected and = 80,00 and = means . While in the case III = 7,708 and LSD = 6,30 so then > LSD so rejected and = 72,08 and = means . It concluded that .